Becoming someone: Paula Modersohn-Becker, the city and the construction of self - Sabin, Kellie (2023)
Paula Modersohn-Becker (1876-1907) created distinctive modernist images, situated at the intersection of Post-Impressionism and Expressionism. A household name in her native Germany, she is considered to be the first modern woman artist, yet her work is rarely the subject of research in Britain. This thesis interrogates Modersohn-Becker’s self-portraits as loci of self-fashioning and possibility, where the construction of an artist identity can successfully be enacted, despite the disadvantages faced on the grounds of gender during the German Imperial period. Chapter one conceptualises Modersohn-Becker’s mobility through the practice of Wanderjahre, and the closely associated cultural idea of Bildung opens up new ways of interpreting the artist’s early work created in Berlin. Chapter two situates Modersohn-Becker in Paris as the flâneuse: a problematic and contested figure within modernity. Utilising her self-portraits and Parisian street scene sketches, it is argued that that the identity of flâneuse was available to Modersohn-Becker by associating female flânerie with the literary model of Virginia Woolf’s narrator in Street Haunting (1930) as opposed to the paradigmatic archetype represented by Baudelaire’s anxious Man of the Crowd. Chapter three critically assesses three of Modersohn-Becker’s radical self-portraits to explore how female artistic identity can be investigated through the maternal nude, the repressed Other and the Egyptian funerary portrait.